Mediators between Positive and Negative Parenting and Child Depressive and Anxious Symptoms: Findings from a Diverse, At-Risk Sample - Christina M. Rodriguez; Anjali Gowda Ferguson; Samantha Gonzalez (MDPI AG, 2022)
Background: Although children's depressive and anxious symptoms have been broadly construed as internalizing problems, the current study sought to identify factors that may differentially contribute to these two mental health problems in a high-risk sample. Prior research has not adequately tested both depressive versus anxious symptoms simultaneously, nor has it adequately considered the role of negative versus positive parenting simultaneously, thereby neglecting the potential overlap in both sets of constructs. Overlooking such potential statistical overlap obfuscates how factors may differentially contribute to either depressive versus anxious symptoms. Existing research has also focused on lower-risk community samples. Method: The present study investigated whether children's negative self-concept or maladaptive attributional style mediated the link between both negative and positive parenting in a racially diverse, at-risk sample of 65 primary school-age children recruited from mental health agencies. Results: When tested together, more negative parenting, but not less positive parenting, retained direct effects on both depressive and anxious symptoms. Both negative self-concept and maladaptive attributional style fully mediated the association between less positive parenting and children's depressive symptoms, whereas positive self-concept, but not attributional style, mediated between less positive parenting and anxious symptoms. Conclusions: The current findings underscore potential differential intervention targets for these two internalizing problems and highlight the need for future research to consider both depressive and anxious symptoms, and related predictors, simultaneously to control for their shared variance.